(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This research shows the process of creating a blood donation website for Oman. Blood donation is a widespread, crucial, ongoing process, so it is important that this website is easy to use. Several automated blood management systems are available, but none provides an effective algorithm that takes into account variables such as frequency of donation, donation date, and gender. In Oman, the Ministry of Health maintains a blood bank and keeps donors informed about the need for blood through a website. They also inform donors and the wider public where and when is their next blood donation event. The website’s main goals are to educate the community about the benefits of blood donation. It also manages donor and receiver documentation and encourages voluntary blood donation by providing easy access to information about blood types and blood distribution in various hospitals in Oman, based on hospital needs.